Female multiple victimization: life stories, depression and coping strategies - Caridade, Sónia (2015)
Research suggests the existence of a relationship between multiple victimization and greater symptomatology complexity. However, some women exposed to cumulative adversity do not develop psychological adjustment issues. With that in mind, this study aimed to identify women's coping strategies to deal with lifetime multiple victimization. For such a purpose, thirty semi -structured interviews were conducted with women, focusing on their life stories. The content of the interviews was subjected to thematic analysis. Results revealed that these women used diverse and spontaneous coping strategies. In addition, these coping strategies are heterogeneous and can be labeled as active (e.g., problem solving, self-confidence, search for social support). Moreover, women with and without depressive symptoms mostly report problem-focused coping strategies in face of victimization. In conclusion, results reinforce the need, regarding support processes, to identify and promote coping mechanisms spontaneously activated by the victims in order to favor their psychological adjustment.